Penerapan Pembelajaran Kitab Tuhfatul Athfal dalam Meningkatkan Kefasihan Membaca Al-Qur’an Santri - Mulki, Muhammad Ilham Maulana; Kosim, Ahmad Mulyadi; Alfaien, Noor Isna (Lembaga Yasin AlSys, 2023)
The objectives of this study are to find out whether the application of learning the Book of Tuhfatul Athfal can improve the fluency of reading the Qur'an of students, to find out how the application of learning the Book of Tuhfatul Athfal in the Islamic Boarding School of the Qur'an Al-Furqon Bogor, to determine the supporting and inhibiting factors in improving fluency in reading the Qur'an students of the Al-Qur'an Islamic Boarding School Al-Furqon Bogor. The method used in this study is a qualitative method with a descriptive approach, this research data collection technique uses observation, documentation and interview techniques. The results showed that. the purpose of studying the book of tuhfatul athfal at the Al-Qur'an Al-Furqon Islamic Boarding School is to keep the tongue to avoid mistakes when reading the Qur'an and avoid changing the meaning when reading the Qur'an. Efforts to improve fluency in reading the Qur'an are carried out by the Al-Qur'an Al-Furqon Islamic Boarding School starting at the boarding school entrance stage, namely by testing the reading of the Qur'an which aims to be able to classify new students in its Qur'an class. Supporting factors are teachers who are competent in their fields, obedient students, facilities and infrastructure to support learning, and parents who support their children. Inhibiting factors are learning time that is too narrow, students who do not obey, and interest and willingness in students or students.